Digitalisasi Home Industry Produk Fashion Guna Meningkatkan Pendapatan Keluarga - Mahfudhoh, Dalilah Hotimatul; Pujianto, Wahyu Eko (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2023)
The current digital era has a good impact on MSMEs because it is very helpful in marketing products and has a very wide reach. This of course can make it easier for consumers to meet their needs. Most MSMEs still lack knowledge about digital marketing to increase the competitiveness of product sales. This service activity for Hotimah Fashion MSME actors is used to make sales widely through the use of digital marketing. Besides that, digital marketing is also very helpful in the economy, especially in increasing family income which is carried out in this service activity. In this service activity the method used by the author is: (1) the planning stage (2) the planning stage (3) the monitoring stage. Providing assistance to business management related to what social media is currently trending that can be used to increase knowledge and sales competitiveness. The activity lasted for approximately one month. This activity is in the form of making a logo, how to log in to social media and marketing on social media. The results of the activities carried out are the creation of media accounts and product sales marketing to increase knowledge and increase product sales so as to increase the competitiveness of MSMEs